Systemic therapy for advanced cholangiocarcinoma: divergences in global guidelines and regional clinical implementation - LI Chun, MA Zuyi, SUN Jia, LI Binglu (Waike lilun yu shijian)
Cholangiocarcinoma (CCA) is a group of malignant tumors arising from the biliary epithelium, with systemic therapy serving as the primary treatment approach for patients with advanced disease. In recent years, advances in molecular classification and targeted therapy have led to rapid updates in treatment guidelines for CCA. This review summarized recent progress in systemic treatment strategies for advanced CCA and the relevant recommendations in both international and domestic guidelines, aiming to provide evidence-based references for clinical management and decision-making in patients with CCA.